Evolutionarily distant I domains can functionally replace the essential ligand-binding domain of Plasmodium TRAP - Klug, Dennis; Göllner, Sarah; Kehrer, Jessica; Sattler, Julia M.; Strauss, Léanne; Singer, Mirko; Lu, Chafen; Springer, Timothy A; Frischknecht, Friedrich (eLife, 2020)
Inserted (I) domains function as ligand-binding domains in adhesins that support cell adhesion and migration in many eukaryotic phyla. These adhesins include integrin αβ heterodimers in metazoans and single subunit transmembrane proteins in apicomplexans such as TRAP in Plasmodium and MIC2 in Toxoplasma. Here we show that the I domain of TRAP is essential for sporozoite gliding motility, mosquito salivary gland invasion and mouse infection.